Free radical grafting of methyl methacrylate onto ethylene-propylene amorphous copolymer - Tomašek, Ljubica (Array, 2009)
Summary: This study investigated the free radical graft copolymerization of methyl methacrylate (MMA) onto amorphous poly(ethylene-co-propylene) (EPC) in toluene solution, when using benzoyl peroxide (BPO) and 2,2´-azobisizobutyronitrile (AIBN) initiators over a wide composition and temperature range. Graft copolymer formation was verified by selective solvent extraction, infrared spectroscopy, and the turbidimetric titration method. Besides graft copolymerization, the homopolymerization reaction of vinyl monomer takes place as well. It was found that grafting is more efficiently induced by BPO, as compared to AIBN. The grafting efficiency (GE) decreased with increasing polymerization temperature and, more significantly, with the increasing MMA concentration. The GE steadily decreased from 90 % to about 30 % over a two hours reaction period at 90 °C reaction temperature, in response to increasing MMA concentration from 0.2 to 1.8 mol dm–3 at a constant EPC concentration of 60 g dm–3. A reaction temperature increase from 70 °C to 95 °C caused a decrease in GE from ~100 % to 75 %. The obtained graft copolymers were characterized for molecular weight distribution and viscometric behavior in dilute xylene solutions and compared with corresponding EPC/PMMA physical mixtures